Analysis of the Relationship of Blood Glucose Levels with Total Cholesterol and Age of Diabetes Mellitus Patients - Oktaviana, Elisa; Nadrati, Bahjatun; Fitriani, Ade (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: One of the chronic complications of diabetes mellitus is fat metabolism disorders. The occurrence of dyslipidemia is a major disorder of fat metabolism in people with diabetes mellitus. Indonesia also faces a diabetes threat situation similar to the world. Objective: The objective of this study was to analyze the relationship between Blood Glucose levels and total cholesterol and the age of patients with diabetes mellitus in the working area of ??the Gunungsari Public Health Center. Method: This research is an observational analytic study with a cross-sectional study design. Result: The results that have a strong relationship with Blood Glucose Levels from the most significant t-count value are X2 Age, which is 5.598 with a coefficient value of 0.000 and has a smaller p-value of 0.029, where p-value <0.05. Therefore, it can be concluded that the stronger relationship with Blood Glucose Levels when X2 is Age compared to X1, namely Total Cholesterol Levels, which have a p-value of 0.522, which has an insignificant value. Conclusion and recommendation: It is necessary to educate the public that non-transmit diseases can be prevented by keeping blood glucose levels and blood fat levels within normal limits by avoiding a diet high in sugar and fat and increasing physical activity